On the independence of hydrogen production from methanogenic suppressor in olive mill wastewater - Gonçalves, Marta R. (2014)
Anaerobic degradation of olive mill wastewater (OMW) at concentrations ranging from 2 to 100 g/L of chemical oxygen demand (COD) was assessed in batch assays. Methane was the main final product obtained for the lower concentrations tested. For 25 g COD/L, H2 was temporarily produced, albeit H2 depletion occurred, likely due to homoacetogenesis, since acetate was formed concomitantly. Hydrogen was produced and accumulated permanently in the assays containing 50 g COD/L of OMW. Methanogenesis and homoacetogenesis were naturally inhibited, suggesting that hydrogen recovery from OMW can be performed without the addition of methanogenic suppressors such as 2-bromoethanosulfonate. This fact opens new perspectives for the utilization of high OMW concentrations in a two-stage valorisation process combining biohydrogen and biomethane production.